Diseases of the Liver in Children Evaluation and Management - Murray, Karen F.; Murray, Karen F.; Horslen, Simon.; Horslen, Simon. (Springer New York : Imprint: Springer, 2014)
Diseases of the Liver in Children: Evaluation and Management provides a comprehensive, state-of-the art review of pediatric liver disease, with a practical approach useful for the primary care provider or general gastroenterologist.  With an emphasis on tables and images, this book serves as a reference for understanding basic hepatic processes and the significance of laboratory findings. It also discusses the state of the art of diagnosis and treatment of diseases that affect the pediatric liver.  The text captures the key elements of treatment and monitoring important for the primary care provider partnering in the care of these patients with pediatric hepatologists. The current state of transplantation and other surgical approaches are also discussed.  The importance of aggressive bowel rehabilitation in the prevention of end-stage total parenteral nutrition-induced liver disease is also covered.        Written by experts in their fields and including the most up to date clinical information,  Diseases of the Liver in Children: Evaluation and Management serves as a very useful resource for physicians.